Authorship Proliferation of Research Articles in Top 10 Orthopaedic Journals: A 70-Year Analysis. (September 2021) - Lutnick, Ellen; Cusano, Antonio; Sing, David; Curry, Emily J.; Li, Xinning
Abstract : Introduction: Scholarly impact has been used to measure faculty productivity and academic contribution throughout academia. Traditionally, the number of articles authored has been the primary metric for scholarly impact regarding academic promotion and reputation. We hypothesize that over time, the nature of authorship has evolved to include more authors per research article throughout the history of orthopaedic literature. Methods: Bibliometric data for all original research article abstracts were extracted from PubMED for the 10 highest rated H5-index orthopaedic clinical journals (" American Journal of Sports Medicine, " " Journal of Bone and Joint Surgery American Volume, " " Clinical Orthopaedics and Related Research " Spine, " " Knee Surgery, Sports Traumatology, Arthroscopy, " " Journal of Arthroplasty, " " Arthroscopy, " " The Spine Journal, " " European Spine Journal, " and " Journal of Bone and Joint Surgery British Volume/Bone & Joint Journal "). The number of authors per article was then analyzed over time using the Cochran-Armitage trend test. Results: A total of 106, 529 original articles were analyzed over a 70-year period. The number of authors increased significantly over time from a mean of 1.4 authors (SD: 0.62) in 1946 to 5.7 authors (SD: 3.1) in 2019, representing an average relative increase of 4.3% per year ( P < 0.05). The three oldest journals had the lowest average authors ( Journal of Bone and Joint Surgery Am Volume : 1946, mean 3.7 authors [SD: eight]; Journal of Bone and Joint Surgery Br Volume/Bone & Joint Journal : 1948, mean: 3.6 authors [SD: 7.5]; Clinical Orthopaedics and Related Research : 1963, mean 3.3 authors [SD: 2.9]). The three newest journals had the highest average authors ( European Spine Journal : 1992, mean 5.3 authors [SD: 3.3]; Knee Surgery, Sports Traumatology, Arthroscopy : 1993, mean 5.5 authors [SD: 6.7 authors; The Spine Journal : 2003, mean 5.2 authors [SD: 3.6]). Discussion: Original research articles published in orthopaedic academic journals have experienced an increase in authorship over time. Although our data cannot explain what has driven this change, increasing cooperation between collaborators may represent less contribution per author over time.